2012
DOI: 10.1021/jf300601z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eriodictyol on Glucose Uptake and Insulin Resistance in Vitro

Abstract: Eriodictyol [2-(3,4-dihydroxyphenyl)-5,7-dihydroxy-2,3-dihydrochromen-4-one] is a flavonoid with anti-inflammatory and antioxidant activities. Because inflammation and oxidative stress play critical roles in the pathogenesis of diabetes mellitus, the present study was designed to explore whether eriodictyol has therapeutic potential for the treatment of type 2 diabetes. The results show that eriodictyol increased insulin-stimulated glucose uptake in both human hepatocellular liver carcinoma cells (HepG2) and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 38 publications
2
71
0
Order By: Relevance
“…Both 300 µM propionic acid and 500 µM valeric acid increased significantly insulin-stimulated glucose uptake by 85.1% (Δ to insulin-treated) and 74.8%, respectively. A PPARγ agonist, rosiglitazone as a positive control [21][23], increased significantly both basal by 60.0% and insulin-stimulated glucose uptake by 170.3%. However, in the case of rosiglitazone, the increasing rate of glucose uptake merely by insulin was about 110.3% (Δ between insulin-stimulated and basal glucose uptake).…”
Section: Resultsmentioning
confidence: 99%
“…Both 300 µM propionic acid and 500 µM valeric acid increased significantly insulin-stimulated glucose uptake by 85.1% (Δ to insulin-treated) and 74.8%, respectively. A PPARγ agonist, rosiglitazone as a positive control [21][23], increased significantly both basal by 60.0% and insulin-stimulated glucose uptake by 170.3%. However, in the case of rosiglitazone, the increasing rate of glucose uptake merely by insulin was about 110.3% (Δ between insulin-stimulated and basal glucose uptake).…”
Section: Resultsmentioning
confidence: 99%
“…10,18 Li et al 10 reported that eriodictyol elevated the activities of SOD, CAT, and GPx, as well as inhibited the production of malondialdehyde, thiobarbituric acid reactive substances (TBARS), TNF-α and IL-1β in kidney tissues. 19 Moreover, eriodictyol attenuates the degree of retinal inflammation and plasma lipid peroxidation, and preserves the blood-retinal barrier (BRB) integrity in streptozotocin-induced diabetic rats. In addition, eriodictyol increased insulin-induced glucose uptake in human hepatocellular liver carcinoma cells (HepG2) and differentiated 3T3-L1 adipocytes under HG condition.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with eriodictyol suppressed diabetes with upregulation of mRNA expression of PPARγ2 and adipocyte-specific fatty acid-binding protein as well as the protein levels of PPARγ2 in differentiated 3T3-L1 adipocytes. Furthermore, eriodictyol reactivated Akt in HepG2 cells with HG-induced insulin resistance [103]. …”
Section: Natural Anti-diabetic/inflammatory Bioactive Compounds Anmentioning
confidence: 99%